The handbook of global energy policy - Goldthau, Andreas (Chichester, West Sussex : Wiley-Blackwell, 2013)
This is the first handbook to provide a global policy perspective on energy, bringing together a diverse range of international energy issues in one volume. Maps the emerging field of global energy policy both for scholars and practitioners; the focus is on global issues, but it also explores the regional impact of international energy policiesAccounts for the multi-faceted nature of global energy policy challenges and broadens discussions of these beyond the prevalent debates about oil supplyAnalyzes global energy policy challenges across the dimensions of mark.
IntroductionEnergy Poverty, Inequality, and Development; Energy Security, Food, and Water; Geopolitical Reconfiguration: The Scramble for African Resources; Food and Energy; Energy and Water Policy; Impact of Resource Extraction on Development in Producing Countries; Changing Landscape in Oil Production; Turning Energy Extraction into Development; Policy Options and Development Impact; Revenue Management; Governance Responses; Conclusions; References; Part II Global Energy and Markets; Chapter 5 The Oil Market: Context, Selected Features, and Implications; Introduction.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Energy policy; Energy policy; BUSINESS & ECONOMICS -- Industries -- Energy; SCIENCE -- Energy; TECHNOLOGY & ENGINEERING -- Power Resources -- General; Energy policy; Electronic books